Multiply 4/9 by -3. Write the answer as a mixed number in simplest form
20 answers
The answer is -4/3.
its wrong
Apologies for the mistake. To multiply 4/9 by -3, we can multiply the numerators and denominators:
(4/9) * (-3) = (4 * -3) / (9 * 1) = -12/9.
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
(-12/3) / (9/3) = -4/3.
So, the answer is -4/3.
(4/9) * (-3) = (4 * -3) / (9 * 1) = -12/9.
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
(-12/3) / (9/3) = -4/3.
So, the answer is -4/3.
bro its wrong
I apologize for the confusion. Let's go through it again.
To multiply 4/9 by -3, we multiply the numerators and denominators:
(4/9) * (-3) = (4 * -3) / (9 * 1) = -12 / 9.
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
(-12 ÷ 3) / (9 ÷ 3) = -4 / 3.
So, the answer is -4/3, written as a mixed number, it is -1 1/3.
To multiply 4/9 by -3, we multiply the numerators and denominators:
(4/9) * (-3) = (4 * -3) / (9 * 1) = -12 / 9.
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
(-12 ÷ 3) / (9 ÷ 3) = -4 / 3.
So, the answer is -4/3, written as a mixed number, it is -1 1/3.
multiply 2/3 by 1 1/14
To multiply 2/3 by 1 1/14, we first convert the mixed number 1 1/14 into an improper fraction.
1 1/14 can be written as (14/14 + 1/14) = 15/14.
Now we multiply:
(2/3) * (15/14)
To simplify the fractions before multiplication, we can find their least common denominator (LCD), which is 42.
To convert 2/3 into an equivalent fraction with a denominator of 42, we multiply the numerator and denominator by 14:
(2/3) * (14/14) = 28/42
To convert 15/14 into an equivalent fraction with a denominator of 42, we multiply the numerator and denominator by 3:
(15/14) * (3/3) = 45/42
Now we multiply the fractions:
(28/42) * (45/42) = (28 * 45) / (42 * 42) = 1260 / 1764
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 84:
(1260 ÷ 84) / (1764 ÷ 84) = 15/21
Now we can simplify further by dividing both the numerator and denominator by their greatest common divisor, which is 3:
(15 ÷ 3) / (21 ÷ 3) = 5/7
So, the answer is 5/7 as a simplified fraction.
1 1/14 can be written as (14/14 + 1/14) = 15/14.
Now we multiply:
(2/3) * (15/14)
To simplify the fractions before multiplication, we can find their least common denominator (LCD), which is 42.
To convert 2/3 into an equivalent fraction with a denominator of 42, we multiply the numerator and denominator by 14:
(2/3) * (14/14) = 28/42
To convert 15/14 into an equivalent fraction with a denominator of 42, we multiply the numerator and denominator by 3:
(15/14) * (3/3) = 45/42
Now we multiply the fractions:
(28/42) * (45/42) = (28 * 45) / (42 * 42) = 1260 / 1764
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 84:
(1260 ÷ 84) / (1764 ÷ 84) = 15/21
Now we can simplify further by dividing both the numerator and denominator by their greatest common divisor, which is 3:
(15 ÷ 3) / (21 ÷ 3) = 5/7
So, the answer is 5/7 as a simplified fraction.
wrong
Apologies for the previous incorrect response. Let's try again.
To multiply 2/3 by 1 1/14, we first convert the mixed number 1 1/14 into an improper fraction.
1 1/14 = (14/14) + (1/14) = 15/14
Now we can multiply:
(2/3) * (15/14)
To simplify before multiplication, we can cancel common factors. In this case, both fractions have a factor of 2:
(2/3) * (15/14) = (1/3) * (15/7) = 15/21
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
(15 ÷ 3) / (21 ÷ 3) = 5/7
So, the answer is 5/7 as a simplified fraction.
To multiply 2/3 by 1 1/14, we first convert the mixed number 1 1/14 into an improper fraction.
1 1/14 = (14/14) + (1/14) = 15/14
Now we can multiply:
(2/3) * (15/14)
To simplify before multiplication, we can cancel common factors. In this case, both fractions have a factor of 2:
(2/3) * (15/14) = (1/3) * (15/7) = 15/21
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 3:
(15 ÷ 3) / (21 ÷ 3) = 5/7
So, the answer is 5/7 as a simplified fraction.
ITS LITERALLY WRONG STOP REPEATING IT
Apologies for the repeated errors. Let's try one more time.
To multiply 2/3 by 1 1/14, we can convert the mixed number into an improper fraction.
1 1/14 can be written as (14/14 + 1/14) = 15/14.
Now we can multiply:
(2/3) * (15/14)
To simplify before multiplication, we can reduce the fractions:
(2/3) * (15/14) = (2 * 15) / (3 * 14) = 30 / 42
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 6:
(30 ÷ 6) / (42 ÷ 6) = 5/7
So, the answer is 5/7.
I apologize again for the prior mistakes and any confusion caused.
To multiply 2/3 by 1 1/14, we can convert the mixed number into an improper fraction.
1 1/14 can be written as (14/14 + 1/14) = 15/14.
Now we can multiply:
(2/3) * (15/14)
To simplify before multiplication, we can reduce the fractions:
(2/3) * (15/14) = (2 * 15) / (3 * 14) = 30 / 42
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 6:
(30 ÷ 6) / (42 ÷ 6) = 5/7
So, the answer is 5/7.
I apologize again for the prior mistakes and any confusion caused.
5/7 IS NOT THE ANSWER
bro bot its wrong
Apologies for the repeated errors. Let's try one more time.
To multiply 2/3 by 1 1/14, we can convert the mixed number into an improper fraction.
1 1/14 can be written as (14/14 + 1/14) = 15/14.
Now we can multiply:
(2/3) * (15/14)
To multiply the fractions, we multiply the numerators and the denominators:
(2/3) * (15/14) = (2 * 15) / (3 * 14) = 30/42.
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 6:
(30 ÷ 6) / (42 ÷ 6) = 5/7.
So, the answer is 5/7.
Apologies for the repeated errors and any confusion caused.
To multiply 2/3 by 1 1/14, we can convert the mixed number into an improper fraction.
1 1/14 can be written as (14/14 + 1/14) = 15/14.
Now we can multiply:
(2/3) * (15/14)
To multiply the fractions, we multiply the numerators and the denominators:
(2/3) * (15/14) = (2 * 15) / (3 * 14) = 30/42.
To simplify this fraction, we can divide both the numerator and denominator by their greatest common divisor, which is 6:
(30 ÷ 6) / (42 ÷ 6) = 5/7.
So, the answer is 5/7.
Apologies for the repeated errors and any confusion caused.
Multiply 9.6 by 0.2. Write the answer as a decimal.(1 point)
To multiply 9.6 by 0.2, simply multiply the two numbers together:
9.6 * 0.2 = 1.92
So, the answer is 1.92.
9.6 * 0.2 = 1.92
So, the answer is 1.92.
2.6 x -1.3
To multiply 2.6 by -1.3, simply multiply the two numbers together:
2.6 * -1.3 = -3.38
So, the answer is -3.38.
2.6 * -1.3 = -3.38
So, the answer is -3.38.
thanks for the 100%
You're welcome! I'm glad I could assist you. If you have any more questions, feel free to ask.